MALE FEMINIST TOKOH UTAMA DALAM NOVEL A DAN Z KARYA ERLIS KURNIYANTI - Dwi Ana, Anggita Cucu; Hidayatullah, Syarif (LPPM Universitas PGRI Silampari Lubuklinggau, 2024)
Studies on men's concern, kindness and emancipation towards women are still rarely carried out even though there are many novels that provide new views on male feminist patterns. For this reason, this research aims to describe the form of the main male feminist characters in the novels A and Z written by young writers. This research uses a qualitative method by analyzing the text contained in the novel created by author Erlis Kurniyanti with the title novel A and Z, with a thickness of 376 pages, first printing January 2022, second printing March 2022, third printing May 2022, fourth printing November 2022, and published by CloudBooks. The results of this research were the discovery of attitudes and behavior that lead to male feminism, including: (1) men are very concerned about fulfilling women's religious needs, women's physical needs, and women's role division needs. (2) men tolerate in the form of fulfilling women's needs to be heard. (3) cultural men in the form of upholding local wisdom values ​​regarding women and upholding religious values ​​regarding women. The novels a and z by Erlis Kurniyanti show more of the attitudes and behavior of male feminists. Men are very concerned with fulfilling women's religious needs.